Keberlanjutan Wisata Kethek'an Ngujang: Kajian Eksistensi dan Pengelolaan Destinasi Budaya Lokal di Kabupaten Tulungagung - Arshaira Aisyah Irsaniyah; Dwi Riadhotul Nisa; Ahmad Roihan Warda; Binti Hadziqotun Nashihah; Muhammad Ikhwanuddin; Regita Cahyani Sukma Dewi; Risalatul Farihah (Tamasya : Jurnal Pariwisata Indonesia, 2026)
Kethek’an Ngujang Tourism, located in Ngujang Village, Tulungagung Regency, is a unique cultural tourism destination characterized by a colony of long-tailed macaques living harmoniously within a cemetery area, reflecting strong historical, cultural, and spiritual values. This study aims to analyze the existence of Kethek’an Ngujang Tourism, identify factors influencing its sustainability, and examine destination management efforts in maintaining its continuity. This research employs a descriptive qualitative method through field observations, in-depth interviews, and documentation. The findings show that the tourism site remains active and continues to attract visitors despite its functional transformation from a nature-based attraction into a religious and pilgrimage tourism destination. Its sustainability is supported by ecological, cultural, historical, and local belief factors, harmonious human–macaque interactions, and a strategic location. However, destination management still faces several challenges, such as limited infrastructure, weak institutional support, low community participation, and suboptimal government involvement. Sustainable management requires stronger synergy between government, local communities, and stakeholders through institutional strengthening, the establishment of Tourism Awareness Groups (Pokdarwis), improved facilities, and the preservation of cultural values and local wisdom. This study contributes to the development of sustainable cultural tourism and provides practical recommendations for destination management based on local wisdom.